2002
DOI: 10.1164/ajrccm.165.3.2106050
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Poly(ADP-Ribose) Polymerase-1 Is a Central Mechanism of Lipopolysaccharide-Induced Acute Lung Inflammation

Abstract: Recent studies demonstrated that activation of the nuclear enzyme poly(ADP-ribose) polymerase-1 (PARP-1) by oxidant-mediated DNA damage is an important pathway of tissue injury in conditions associated with oxidative stress. Using a dual approach of PARP-1 suppression, by genetic deletion or pharmacological inhibition with the phenanthridinone PARP inhibitor PJ-34, we now demonstrate an essential role of PARP-1 in the development of pulmonary inflammation induced by lipopolysaccharide (LPS). PARP-1+/+ and PARP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
152
2
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(168 citation statements)
references
References 38 publications
10
152
2
4
Order By: Relevance
“…Our results are in agreement with literature that describes adenosine and inosine as critical molecules involved in the regulation of inflammatory and immune processes [20,[30][31][32]. Adenosine accumulates in the extracellular space in response to metabolic stress and cell damage, and elevations in extracellular adenosine are found in conditions of ischemia, hypoxia, inflammation, and trauma [33,34].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are in agreement with literature that describes adenosine and inosine as critical molecules involved in the regulation of inflammatory and immune processes [20,[30][31][32]. Adenosine accumulates in the extracellular space in response to metabolic stress and cell damage, and elevations in extracellular adenosine are found in conditions of ischemia, hypoxia, inflammation, and trauma [33,34].…”
Section: Discussionsupporting
confidence: 92%
“…Inosine also is known to exert wide raging anti-inflammatory effects that include inhibition of pro-inflammatory cytokine, chemokine production, protection in septic shock, colitis, and acute lung injury [31,45,46]. Some studies have shown that inosine can stimulate adenosine A 2A receptors and is protective in models of Concanavalin A-induced liver damage, endotoxininduced sepsis [20,47], and TNBS-induced colitis [21].…”
Section: Discussionmentioning
confidence: 99%
“…In the lungs, PARP plays a key role in the microvascular platelet-endothelial cell interaction induced by endotoxin, acute lung inflammation following intratracheal administration of endotoxin, induction of asthma, an leukocyte recruitment in systemic endotoxemia [6,42,43]. These cellular interactions, tissue inflammatory changes and subsequent alterations in adhesion molecules are likely to be the fundamental basis for the pathogenesis of lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…1C). Alveolar neutrophil accumulation, hyperreactivity and lung damage were also attenuated [69]. PARP-1 gene silencing or inhibition by niacinamide, but not by PJ-34, also diminished IL-1 and MIP-2 expression [69,70].…”
Section: Parp-1 In Lung Disordersmentioning
confidence: 91%
“…In 2002, Liaudet et al [69] demonstrated that the absence of functional PARP-1 reduced LPS-induced cytokine expression (TNF-, MIP-1 and IL-6), NO production, and lipid peroxidation (Fig. 1C).…”
Section: Parp-1 In Lung Disordersmentioning
confidence: 92%